Epidemiology of congenital diaphragmatic hernia in Europe: a register-based study. Issue 2 (19th November 2014) - McGivern, Mark R; Best, Kate E; Rankin, Judith; Wellesley, Diana; Greenlees, Ruth; Addor, Marie-Claude; Arriola, Larraitz; de Walle, Hermien; Barisic, Ingeborg; Beres, Judit; Bianchi, Fabrizio; Calzolari, Elisa; et al.
Abstract : Introduction: Published prevalence rates of congenital diaphragmatic hernia (CDH) vary. This study aims to describe the epidemiology of CDH using data from high-quality, population-based registers belonging to the European Surveillance of Congenital Anomalies (EUROCAT). Methods: Cases of CDH delivered between 1980 and 2009 notified to 31 EUROCAT registers formed the population-based case series. Prevalence over time was estimated using multilevel Poisson regression, and heterogeneity between registers was evaluated from the random component of the intercept. Results: There were 3373 CDH cases reported among 12 155 491 registered births. Of 3131 singleton cases, 353 (10.4%) were associated with a chromosomal anomaly, genetic syndrome or microdeletion, 784 (28.2%) were associated with other major structural anomalies. The male to female ratio of CDH cases overall was 1:0.69. Total prevalence was 2.3 (95% CI 2.2 to 2.4) per 10 000 births and 1.6 (95% CI 1.6 to 1.7) for isolated CDH cases. There was a small but significant increase (relative risk (per year)=1.01, 95% credible interval 1.00–1.01; p=0.030) in the prevalence of total CDH over time but there was no significant increase for isolated cases (ie, CDH cases that did not occur with any other congenital anomaly). There was significant variation in total and isolated CDH prevalence between registers. The proportion of cases that survived to 1 week was 69.3% (1392 cases) for total CDH cases and 72.7% (1107) for isolated cases. Conclusions: This large population-based study found an increase in total CDH prevalence over time. CDH prevalence also varied significantly according to geographical location. No significant association was found with maternal age.